2021
DOI: 10.3390/biomedicines9111549
|View full text |Cite
|
Sign up to set email alerts
|

Sex-Dependent Effects of Eicosapentaenoic Acid on Hepatic Steatosis in UCP1 Knockout Mice

Abstract: Visceral obesity may be a driving factor in nonalcoholic fatty liver disease (NAFLD) development. Previous studies have shown that the omega-3 polyunsaturated fatty acid, eicosapentaenoic acid (EPA), ameliorates obesity in high-fat (HF) fed male, C57Bl/6 mice at thermoneutral conditions, independent of uncoupling protein 1 (UCP1). Our goals herein were to investigate sex-dependent mechanisms of EPA in the livers of wild type (WT) and UCP1 knockout (KO) male and female mice fed a HF diet (45% kcal fat; WT-HF, K… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
1
1

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 59 publications
(89 reference statements)
0
1
0
Order By: Relevance
“…Numerous studies have shown that induction of UCP1 increases thermogenesis in BAT and initiates the browning process in WAT [ 10 ]. UCP1 KO mice exhibited decreased thermogenesis upon cold stimulation [ 11 ] and dramatically increased body weight compared with the wild type during a high fat diet [ 12 ]. Moreover, recent studies have elucidated the mechanism by which ROS directly modifies UCP1 to stimulate thermogenesis [ 13 ].…”
Section: Bat Biomarkers and Batokinesmentioning
confidence: 99%
“…Numerous studies have shown that induction of UCP1 increases thermogenesis in BAT and initiates the browning process in WAT [ 10 ]. UCP1 KO mice exhibited decreased thermogenesis upon cold stimulation [ 11 ] and dramatically increased body weight compared with the wild type during a high fat diet [ 12 ]. Moreover, recent studies have elucidated the mechanism by which ROS directly modifies UCP1 to stimulate thermogenesis [ 13 ].…”
Section: Bat Biomarkers and Batokinesmentioning
confidence: 99%